Bioinformatic and experimental fishing for artemisinin-interacting proteins from human nasopharyngeal cancer cells - Eichhorn, Tolga; Wendler, Astrid; Krauth-Siegel, Renate (Molecular BioSystems, 2012)
Determining interacting cellular partners of drugs by chemical proteomic techniques is complex and tedious. Most approaches rely on activity-based probe profiling and compound-centric chemical proteomics. The anti-malarial artemisinin also exerts profound anti-cancer activity, but the mechanisms of action are incompletely understood. In the present investigation, we present a novel approach to identify artemisinin-interacting target proteins. Our approach overcomes usual problems in traditional fishing procedures, because the drug was attached to a surface without further chemical modification. The proteins identified effect among others, cell cycle arrest, apoptosis, inhibition of angiogenesis, disruption of cell migration, and modulation of nuclear receptor responsiveness. Furthermore, a bioinformatic approach confirmed experimentally identified proteins and suggested a large number of other interacting proteins. Theoretically predicted interaction partners may serve as a starting point to complete the whole set of proteins binding artemisinin.
Gesehen am 25.06.2019